Games user research (Oxford University Press, 2018)
The definitive guide to methods and practices for games user professionals, researchers and students seeking additional expertise or starting advice in the game development industry. It is the go-to volume for everyone working with games, with an emphasis on those new to the field.
10.1093/oso/9780198794844.001.0001
Keywords: Programmierung; Benutzerrückmeldung; Benutzerfreundlichkeit; Design; Computerspiel